Analisis Responsibility Center Guna Memaksimalkan Kinerja tiap Divisi di STIKES RS Anwar Medika di Sidoarjo - Farida, Elis Anita (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2020)
This study aims to analyze the application of responsibility center to the performance of each division in STIKES RS Anwar Medika in Sidoarjo. The design of this study is quantitative using survey methods. Observations were made with a questionnaire instrument with scoring given to educators and students of the achievements of each division STIKES RS Anwar Medika in Sidoarjo. The results of this study illustrate that the performance of the three divisions is sufficient to achieve the vision and mission of the STIKES RS Anwar Medika, but this has not been maximized due to inappropriate strategies. It is known that the number of educators is not balanced with the number of students resulting in a high workload of educators and an impact on the lack of educator productivity in terms of research development. Completeness of laboratory facilities is sufficiently supported so that students can take advantage of research development and knowledge enhancement. Keyword: Responsibility Center, STIKES RS Anwar Medika, vision and mission, performance